PENGEMBANGAN LAYANAN BIMBINGAN DAN KONSELING ISLAM MELALUI PENDAMPINGAN KONSELOR SEBAYA DI PONDOK PESANTREN FADHLUL FADHLAN KECAMATAN MIJEN KOTA SEMARANG - Faiza Algifahmy, Ayu; Kibtiyah, Maryatul; Diah Anjaryani, Wieke; Maulida Khasanah, Rosa (Jurnal Berdaya Mandiri, 2024)
Most of the students at the Fadhlul Fadhlan Mijen Islamic Boarding School in Semarang City are teenagers aged 17-21 years. Adolescence is at the limit of preserving the life of an adult child. His body looks mature but is often treated like an adult and often fails to show maturity such as anxiety, conflict, confusion and frequent self-conflict. This problem is an interesting study to develop. The problem in this service is what is the process of mentoring peer counselors at the Fadhlul Fadhlan Islamic Boarding School, Mijen District, Semarang City? How is the development of Islamic Guidance and Counseling services at the Fadhlul Fadhlan Islamic Boarding School, Mijen District, Semarang City? This service aims to provide training to develop individual skills in peer counseling, as well as being able to foster social relationships in accordance with desires and independence. The service is carried out using the PAR method, where before carrying out this service, the researcher first conducts research in the field. The strategy used in this peer counseling assistance is Focus Group Discussion (FGD), as well as assistance with peer counseling practices. The result of this service is to bring back the students' potential to be able to solve and unravel the problems of their lives, and to be able to synergize with their peers to move forward together in growing their basic potential. Keywords: Islamic Guidance and Counseling, Peer Counselor